Comparing BRIN-BD11 culture producing insulin using different type of microcarriers - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd Yusof, Siti Aishah; Hashim, Yumi Zuhanis Has-Yun; Ahmad Nor, Yusilawati (Springer, 2010)
This research was conducted to examine the growth profile, growth kinetics, and insulinsecretory responsiveness of BRIN-BD11 cells grown in optimized medium on different types of microcarriers (MCs). Comparisons were made on modified polystyrene (Hillex II) and crosslinked polystyrene Plastic Plus (PP) from Solohill Engineering. The cell line producing insulin was cultured in a 25 cm2 T-flask as control while MCs based culture was implemented in a stirred tank bioreactor with 1 L working volume. For each culture type, the viable cell number, glucose, lactate, glutamate, and insulin concentrations were measured and compared. Maximum viable cell number was obtained at 1.47 9 105 cell/mL for PP microcarrier (PPMCs) culture, 1.35 9 105 cell/mL Hillex II (HIIMCs) culture and 0.95 9 105 cell/mL for T-flask culture, respectively. The highest insulin concentration has been produced in PPMCs culture (5.31 mg/L) compared toHIIMCs culture (2.01 mg/L) and T-flask culture (1.99 mg/L). Therefore overall observation suggested that PPMCs was likely preferred to be used for BRIN-BD11 cell culture as compared with Hillex II MCs.